HUBUNGAN PENGETAHUAN IBU DAN ASUPAN MP-ASI BERSUMBER PROTEIN HEWANI DENGAN KEJADIAN STUNTING: (STUDI KASUS PADA ANAK BAWAH DUA TAHUN DI WILAYAH KERJA PUSKESMAS CITANGKIL II KOTA CILEGON) - Lia Pursitawati; Halik Sidik; Muhlisin Muhlisin (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2024)
In Indonesia, stunting is a serious health issue, including at the Citangkil II Community Health Center in Cilegon City. This study aims to analyze the relationship between maternal knowledge and the intake of complementary foods based on animal protein and the incidence of stunting. A case-control design was employed in this study, involving 145 mothers with toddlers aged 6-23 months. Data were collected through interviews to assess maternal nutrition knowledge and complementary food intake, as well as secondary data from measurements of children's height and length to determine stunting status. The results show that 40% of the respondents have good knowledge, and the intake of complementary foods from animal protein sources is quite high, with 33% of toddlers categorized as having good intake. The analysis reveals a significant relationship between maternal knowledge, the type and amount of complementary foods based on animal protein, and stunting (p < 0.05). This study emphasizes the importance of improving maternal nutrition knowledge and the intake of animal protein-based complementary foods in preventing stunting, thereby enhancing children's health and growth.